2019
DOI: 10.1002/ejic.201901016
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Catalyzed Hydrofunctionalization Reactions of Haloalkynes

Abstract: Metal‐catalyzed hydrofunctionalization reactions of alkynes, i.e. the addition of E–H units (E = heteroatom or carbon) across the C≡C bond, are of key importance in modern synthetic chemistry. In recent years, haloalkynes have been successfully involved in these types of transformations, thus opening new atom‐economical routes for the generation, among others, of haloalkenes, a pivotal class of compounds for cross‐coupling processes. In particular, several catalytic systems able to promote the selective additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 138 publications
(120 reference statements)
1
14
0
Order By: Relevance
“…The process, which proceeds under mild conditions and tolerates the presence of several functional groups in the substrates, involves the intermolecular addition of carboxylic acids to iodoalkynes, the latter being activated towards the carboxylate anion attack by π-coordination to the in situ generated gold(I) cation [Au(PPh3)] + . As expected, the carboxylate anion adds selectively to the more electrophilic C-2 carbon of the iodoalkyne [45][46][47] and, as usually observed in the chemistry of π-alkyne-gold complexes [62], the addition takes places in an anti fashion, thus affording the olefinic products 19 in a complete regio-and stereoselective manner. With a couple of representative examples, i.e., the addition of acetic acid to 1-(chloroethynyl)-4-methylbenzene and 1-bromooct-1-yne, the authors also demonstrated the applicability of this procedure for the synthesis of related (Z)-β-chloroenol and Making use of a catalytic system composed of the gold(I) complex [AuCl(PPh 3 )] and the chloride abstractor AgPF 6 , a broad scope procedure for the preparation of acyclic (Z)-β-iodoenol esters was also recently developed by Cadierno and co-workers (Scheme 12) [59][60][61].…”
Section: Au-catalyzed Synthesis Of β-Haloenol Esterssupporting
confidence: 66%
“…The process, which proceeds under mild conditions and tolerates the presence of several functional groups in the substrates, involves the intermolecular addition of carboxylic acids to iodoalkynes, the latter being activated towards the carboxylate anion attack by π-coordination to the in situ generated gold(I) cation [Au(PPh3)] + . As expected, the carboxylate anion adds selectively to the more electrophilic C-2 carbon of the iodoalkyne [45][46][47] and, as usually observed in the chemistry of π-alkyne-gold complexes [62], the addition takes places in an anti fashion, thus affording the olefinic products 19 in a complete regio-and stereoselective manner. With a couple of representative examples, i.e., the addition of acetic acid to 1-(chloroethynyl)-4-methylbenzene and 1-bromooct-1-yne, the authors also demonstrated the applicability of this procedure for the synthesis of related (Z)-β-chloroenol and Making use of a catalytic system composed of the gold(I) complex [AuCl(PPh 3 )] and the chloride abstractor AgPF 6 , a broad scope procedure for the preparation of acyclic (Z)-β-iodoenol esters was also recently developed by Cadierno and co-workers (Scheme 12) [59][60][61].…”
Section: Au-catalyzed Synthesis Of β-Haloenol Esterssupporting
confidence: 66%
“…Alkynes are a pivotal class of compounds in organic chemistry and their electrophilic activation by transition metals has become a mainstay in the toolbox of synthetic chemists, biochemists, and materials scientists [1][2][3]. In this context, the metal-catalyzed hydrofunctionalization of alkynes, i.e., the addition of Y-H units (Y = heteroatom-or carbon-centered nucleophile) across the C≡C bond, has emerged in the last decades as one of the most powerful tools to access functionalized olefins in an atom-economical manner, its intramolecular version allowing also the rapid assembly of a wide range of heterocyclic and carbocyclic compounds (see Scheme 1) [4][5][6][7][8][9]. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of transition metal compounds (complexes, salts, or nanoparticles) are known to promote the addition of Y-H units to alkynes by π-activation of C≡C bond, the regio-and stereoselectivity (syn-or anti-type addition) of the process being strongly dependent on the nature of the reactants, catalyst, and reaction conditions employed, and a priori difficult to predict, particularly in the case of non-symmetrically substituted alkynes (up to four isomeric products can be potentially formed) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relative stability, ease of handling and the presence of reactive sites, bromoacetylenes are widely applied in synthetic organic chemistry. They are known to be involved in various transformations including homo- and cross-coupling [ 1 7 ], addition [ 1 , 8 9 ], cycloaddition [ 1 , 10 11 ] and other reactions . Of particular synthetic value is the addition to the triple bond of bromoacetylenes to provide vinyl adducts, which can undergo numerous transformations.…”
Section: Introductionmentioning
confidence: 99%